Exploring the performance of responsible companies in G20 during the COVID-19 outbreak - El Khoury, Rim (2022)
An uphill question of whether Environmental, Social, and Governance (ESG) directly impact firms' financial performance (FP) continues to vacillate between two opponent streams. In the present study, we argue that COVID-19 is an extreme event where the effect of ESG sharply manifests. We rely on cross-sectional data in the context of G20 countries for the year 2020. To avoid biased results due to governments support, we integrate four novel metrics provided by the Oxford Coronavirus Government Response Tracker (OxCGRT). We run sequential regressions (OLS; and quartiles to account for the Ingrained Income Bias (IIB) and ESG scores). We also perform robustness tests and account for the interaction between ESG and cash level. Our models were subsequently replicated for each ESG pillar. Findings indicate that ESG is beneficial during COVID-19, but the reward appears to be closely tied up to specific aspects of ESG, income level, and firm-specific variables. Results contribute to the burgeoning literature on ESG during COVID-19 by reflecting on firms’ key attributes and the preponderance of government support